2013
DOI: 10.1261/rna.037630.112
|View full text |Cite
|
Sign up to set email alerts
|

Computational detection of abundant long-range nucleotide covariation inDrosophilagenomes

Abstract: Functionally important nucleotide base-pairing often manifests itself in sequence alignments in the form of compensatory base changes (covariation). We developed a novel index-based computational method (CovaRNA) to detect long-range covariation on a genomic scale, as well as another computational method (CovStat) for determining the statistical significance of observed covariation patterns in alignment pairs. Here we present an all-versus-all search for nucleotide covariation in Drosophila genomic alignments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…First, they confine the search space to evolutionarily conserved regions, which at least partly reduces the complexity and improves specificity. Second, at least hypothetically, they gain statistical power through observing compensatory changes in covarying positions [ 52 , 53 , 54 , 55 , 56 ]. These ideas, which stem from covariance models [ 57 ], have been remarkably successful in the discovery of riboswitches [ 58 ].…”
Section: Predicting Long-range Rna Structurementioning
confidence: 99%
See 1 more Smart Citation
“…First, they confine the search space to evolutionarily conserved regions, which at least partly reduces the complexity and improves specificity. Second, at least hypothetically, they gain statistical power through observing compensatory changes in covarying positions [ 52 , 53 , 54 , 55 , 56 ]. These ideas, which stem from covariance models [ 57 ], have been remarkably successful in the discovery of riboswitches [ 58 ].…”
Section: Predicting Long-range Rna Structurementioning
confidence: 99%
“…However, the examples from mammalian and insect genes ( Table 1 ) show little or no variation, suggesting that functional structures evolve under strong negative selection [ 38 ]. In addition, compensatory patterns can arise not only to maintain base-pairing interactions, but also as a result of synchronized mutations that preserve binding of a common interaction partner in antisense genomic orientation [ 53 ]. An example of this is RP11-439A17.4 long non-coding RNA, which is located in antisense to HIST2H2BA gene and overlaps a transcription factor binding site, which also occurs in almost all human histone genes in sense orientation, resulting in a seeming compensatory pattern [ 39 ].…”
Section: Predicting Long-range Rna Structurementioning
confidence: 99%
“…255 CovaRna and CovStat were developed to explore long-range covarying RNA interaction networks using whole genome alignments. 256 MC-sym builds all-atom structures using the 3D version of the nucleotide cyclic motif (NCM) fragments which are not only extracted from known RNA 3D structures but also built on the fly if necessary, but this method is limited to short RNAs requiring 2D structures as input due to the limited NCM fragments for large, complex NCM motifs, such as six-way junctions and kissing loops. There are several programs that combine 2D and 3D analyses together, such as iFoldRNA, Vfold, Nanotiler (Figure 16), RNA2D3D, and FR3D.…”
Section: D/3d Modeling/prediction Of Desired Rna Nanoparticlesmentioning
confidence: 99%
“…Correlated mutations have also been used successfully to identify DNA-binding domains and sites of transcription factors, such as the MerR-family proteins ( 13 ). Extended to whole genomes, this concept was used in the Drosophila genus ( 14 ). In this study, investigators searched for long-range covariation clusters on a genomic scale based on genome-triple ‘fingerprints’ and reported that compensatory mutations suggest long range interactions between exons of mRNAs and also between noncoding RNAs.…”
Section: Introductionmentioning
confidence: 99%